A review exploring coach knowledge, attitudes/beliefs and behaviours towards low energy availability in athletes - Hamer, J.; Desbrow, B.; Irwin, C. (International Journal of Sports Science & Coaching, 2023)
Coaches are important figures of influence with potential to create environments that influence athlete health and performance outcomes. Ideally, coaches provide supportive environments that lead to performance optimisation and long-term health. Coaches who employ language and behaviours that overemphasise body composition and/or provide misinformed nutrition advice may predispose athletes to low energy availability (LEA) and the associated health consequences. Having a clear understanding of current knowledge, attitudes and beliefs of coaches with regard to LEA is required to guide future coach education/support initiatives to optimise athlete health and performance. Thus, the aim of this investigation was to systematically review published literature regarding coach knowledge, attitudes/beliefs and behaviours of LEA. Data from 20 eligible studies was extracted into predetermined categories according to coach `knowledge`; `attitudes/ beliefs`; and `behaviours` regarding LEA/Relative Energy Deficiency in Sport/Female Athlete Triad and/or eating disorders and/or disordered eating. Any single study could provide outcomes to inform one or multiple of these categories. The majority of results were drawn from studies conducted prior to LEA being defined as a concern for athlete health, which limited our understanding of the contemporary knowledge, attitudes/eliefs and behaviours of coaches on this important issue. That said, indications of gaps in coach knowledge and the employment of inappropriate attitudes/beliefs and behaviours regarding issues associated with LEA were evident. An opportunity exists for key stakeholders to develop comprehensive coach education frameworks, which equip coaches with the adequate capability, opportunity and motivation to support athlete health and avoid the consequences of LEA.